Base64 Sebagai Kunci Keamanan pada One Time Pad (OTP) - Oris Krianto Sulaiman; Khairuddin Nasution; Satria Yudha Prayogi (Universitas Negeri Medan, 2020)
Message security in communication is very important to maintain the confidentiality and integrity of messages. The message that is sent must be conveyed in its entirety and only delivered according to its purpose. One Time Pad or OTP is an algorithm that can encrypt messages into ciphertext so that message security can be guaranteed. OTP is a symmetric cryptographic algorithm, that is, the key for encryption and decryption is the same. To perform encryption, the OTP plaintext length must be the same as the key length. This will make it difficult when there is a very long length of plaintext, so the key must also adjust it. OTP keys also have a weakness if a key has been used more than once. Therefore a key builder is needed. In this research, the key generator used is base64. Base64 is used to change the bits of plaintext that will be used by OTP. In this study, base64 can encode plaintext to be used as an OTP key so that it succeeded in making the key generator from base64 encoding.